A case study on the role of interior design in promoting well-being among users of selected barangay health centers within Metro Manila - Villanueva, Decena D. (College of Home Economics, University of the Philippines Diliman, 2019)
This case study research sought to determine the role of interior design in the promotion of well-being among users of three (3) selected barangay health centers located in Marikina, Caloocan and Manila. A qualitative approach was utilized through observations, in depth interviews, surveys, photo documentation and on-site measurements. Purposive and convenience sampling were applied in the study to select the 60 respondents, categorized accordingly as barangay health workers, patients and guardians. With the goal of examining which built environmental elements negatively and positively affect the users' physical and psychological well-being of the healthcare institution, the study looked into the different building attributes: (1) layout and space planning, (2) lighting, (3) furniture, (4) smell, (5) ventilation, (6) noise level, and (7) decorative elements. The findings suggest that despite the respondents' positive evaluation of their visits and their low priority on the ambience and overall design of the barangay health center, the respondents are much affected by the barangay health center's built environment conditions. For the health workers, the lack of proper ventilation and the allocation of support spaces affect the quality of care they give as well as their productivity. The findings also suggest that the waiting area should be given more attention for patients and guardians who are affected bu issues of privacy and crowding. Results of the study infer that their attitude of making do with what they have as well as having high levels of satisfaction in response to the survey are observed manifestations of their socio-economic status. The observed lack of awareness among the users of the barangay health cneters reiterates that all the more it is important to introduce improved interior spaces in public healthcare facilities.